2020
DOI: 10.3390/cells9102182
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Exercise in Neurodegenerative Diseases: The Potential Role of Extracellular Vesicles

Abstract: Physical activity has systemic effects on the body, affecting almost every organ. It is important not only for general health and wellbeing, but also in the prevention of diseases. The mechanisms behind the therapeutic effects of physical activity are not completely understood; however, studies indicate these benefits are not confined to simply managing energy balance and body weight. They also include systemic factors which are released into the circulation during exercise and which appear to underlie the myr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 226 publications
(234 reference statements)
2
22
0
Order By: Relevance
“…More recently, the analysis of the methylation profile of cfDNA shows that about 32% of cfDNA is derived from granulocytes, 30% from erythrocyte progenitors, 23% from monocytes and lymphocytes, 9% from endothelial cells, and only 6% from other cells including neurons and hepatocytes [ 11 ], while a sub-characterization for exercise released cfDNA has not been conducted yet. We and others found that next to muscle cells, platelets, endothelial cells, and leukocytes, significantly contribute to the pool of EVs released into plasma following physical exercise (reviewed in [ 47 , 62 , 63 , 64 ]). Like for cfDNA, the underlying signaling mechanisms are not fully understood, but an association with shear stress and the activation of coagulative processes are discussed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the analysis of the methylation profile of cfDNA shows that about 32% of cfDNA is derived from granulocytes, 30% from erythrocyte progenitors, 23% from monocytes and lymphocytes, 9% from endothelial cells, and only 6% from other cells including neurons and hepatocytes [ 11 ], while a sub-characterization for exercise released cfDNA has not been conducted yet. We and others found that next to muscle cells, platelets, endothelial cells, and leukocytes, significantly contribute to the pool of EVs released into plasma following physical exercise (reviewed in [ 47 , 62 , 63 , 64 ]). Like for cfDNA, the underlying signaling mechanisms are not fully understood, but an association with shear stress and the activation of coagulative processes are discussed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the complete isolation of ELVs from other EVs becomes paramount. There is growing interest in the topic of SkMEV and proposed EV cargo in response to exercise ( Rome et al, 2019 ; Trovato et al, 2019 ; Vechetti, 2019 ; Murphy et al, 2020 ; Fuller et al, 2020 ). Given the challenge presented in tracking skeletal muscle-derived ELVs, whether miRNA cargo observed immediately following exercise is derived from the exercising muscle remains to be elucidated clearly.…”
Section: Extracellular Vesicles – Potential Mediators Of the Multi-symentioning
confidence: 99%
“…The heterogeneity of EV populations and other bioactive particles in blood faces EV research with numerous challenges and, thus, confuses the determination of EVs released into the circulation upon physical exercise (ExerVs). The modalities of ExerV-release, the putative role in adaptation signaling as well as prospective therapeutic and diagnostic applications were recently highlighted and comprehensively summarized (e.g., Trovato et al, 2019 ; Fuller et al, 2020 ; Vechetti et al, 2020 ). Here, we supplement this body of literature with a compilation of the most relevant technical limitations regarding ExerV isolation and characterization, focusing on sEVs.…”
Section: Introductionmentioning
confidence: 99%